A-BI+: A framework for Augmented Business Intelligence. (September 2020) - Francia, Matteo; Golfarelli, Matteo; Rizzi, Stefano
Abstract: Augmented reality allows users to superimpose digital information (typically, of operational type) upon real-world objects. The synergy of analytical frameworks and augmented reality opens the door to a new wave of situated analytics, in which users within a physical environment are provided with immersive analyses of local contextual data. In this paper, we propose an approach named A-BI + (Augmented Business Intelligence) that, based on the sensed augmented context (provided by wearable and smart devices), proposes a set of relevant analytical queries to the user. This is done by relying on a mapping between the objects that can be recognized by the devices and the elements of the enterprise multidimensional cubes, and also by taking into account the queries preferred by users during previous interactions that occurred in similar contexts. A set of experimental tests evaluates the proposed approach in terms of efficiency, effectiveness, and user satisfaction. Highlights: A recommendation framework for analytical reports exploiting augmented environments. Meaningful recommendations even in case of cold start. A-BI + adapts its recommendations to user behaviors. A-BI + provides different analytical reports by means of embedded differentiation. A large set of tests confirming effectiveness, efficiency and users appreciation.